Obstacle avoidance legged robot - Mohamed Faizan, Basheer Ahmad (2008)
Many mobile robots require an operator’s vision and intelligence for guidance and navigation. Animals use sensory systems such as hearing, and tactile to move freely through their environment. The aim of this project is to develop an avoidance behaviors program for a mobile robot that consists of 8 servo motors that been employed at 4 legs. Each leg contains 2 servo motors, one for X-axis and one for Y-axis. A PIC Microcontroller has been implemented to act as a brain for the robot that controls the walking and turning algorithm. Ultrasonic sensor was also developed to act as an ‘eye’ to the system and tells the brain about existence of obstacle in front. As a resultant, the obstacle avoidance legged robot system is been successfully developed that allows and will navigate the robot to move through the environment freely. But there is a certain limitation for the robot such as the wideness of the area, type of obstacle and surface.